(untitled) (Homoeopathy for All, 2022)
Dr. John Henry Clarke was born in 1853. He was one of the most eminent homoeopaths of England, who devoted his whole life for the advancement of Homoeopathy. He took his degree at Edinburgh University in 1875 as gold medalist in several subjects, followed it up with the M. D. and further academic successes and appointments in 1877. He became a keen follower of Dr. Compton Burnett who was himself in the direct hierarchy of Ruddock. In April 1885, Dr. Burnett edited his last volume of The Homoeopathic World and the next month, May 1885, Dr. Clarke commenced as editor. He was editor of ‘The Homoeopathic World’ for twenty-nine years. He was also a consulting physician to the London Homoeopathic Hospital.